The Influence of Ewom on The Shopee Application on Intention to Purchase Make Over Products - Naufal Moh Shiddiq; Anas Hidayat (PT SOLUSI EDUKASI BERDIKARI, 2024)
The E-commerce phenomenon has shifted and transformed the way conventional marketing works, thus creating a new term in digital marketing, namely eWOM. Online reviews or eWOM have a big impact on consumer purchasing decisions, so this research examines the influence of eWOM on Shopee on intentions to buy local skincare. The research strategy in this study is a survey strategy, which means data collection uses a questionnaire to obtain quantitative data from 400 respondents which is distributed via Google Form. The data analysis technique used to test the hypothesis in this research is the SEM (Structural Equation Modeling) method on the SmartPLS 4.0.6 program. The results of this research show that information quality, information quantity, information credibility have a positive and significant effect on the usefulness of information. The Usefulness of information has an positive and significant effect on the usefulness of information. The usefulness of information has a positive and significant effect on the usefulness of information. The usefulness of information has a positive and significant effect on the usefulness of information adoption. And information adoption has a positive and significant effect on purchase intention.